Efficiency of the work of almond shells as biological carriers in activated sludge aeration tanks: كفاءة عمل قشور اللوز كحوامل بيولوجية في أحواض التهوية بالحمأة المنشطة - Raghad Salim Al-Shalabi, Naeima Ajib, Mahmoud Fattamah (مجلة العلوم الهندسية و تكنولوجيا المعلومات, 2020)
Based on the interest in environmentally friendly materials for wastewater treatment, this research is aimed at evaluating the efficiency of almond shells work as biological carriers in activated sludge aeration tanks, known as the integrated fixed-film activated sludge treatment, a hybrid tank with attached growth and suspended growth is obtained. Almond shells were placed at 7% of the size of the aeration tank throughout the experiment period for about 4 months with a number of indicators such as hydraulic retention time and mixed liquor suspended solids. Two sets of experiments were performed, the first group with a constant hydraulic retention time ( HRT= 4 hours), and mixed liquor suspended solids was changed (500-1000-2000-3000 mg/ L), with the best removal efficiency at MLSS = 2000 mg/ l, by 91.3% and 92.1% for COD and SS respectively. The optimal MLSS concentration was adopted for the second group of experiments where HRT was increased to 5 and 6 hours. As a result, the best chain was found to be MLSS = 2000 mg/ l and HRT = 5 hours, with a removal efficiency of 93.4% and 93.9% for COD and SS respectively. As a result, the rate of return activated sludge was reduced from 100% to 60% and the rate of inflow into the aeration tank was increased due to the reduction HRT from 6 hours to 5 hours compared to conventional activated sludge treatment.
Keywords: حوض هجين; النمو المثبت; النمو المعلق